Structural Equation Models and Mixture Models With Continuous Nonnormal Skewed Distributions. Issue 1 (2nd January 2016) - Asparouhov, Tihomir; Muthén, Bengt
Abstract : In this article we describe a structural equation modeling (SEM) framework that allows nonnormal skewed distributions for the continuous observed and latent variables. This framework is based on the multivariate restricted skew t distribution. We demonstrate the advantages of skewed SEM over standard SEM modeling and challenge the notion that structural equation models should be based only on sample means and covariances. The skewed continuous distributions are also very useful in finite mixture modeling as they prevent the formation of spurious classes formed purely to compensate for deviations in the distributions from the standard bell curve distribution. This framework is implemented in M plus Version 7.2.